2000
DOI: 10.1115/1.1330268
|View full text |Cite
|
Sign up to set email alerts
|

Using Sweep and Dihedral to Control Three-Dimensional Flow in Transonic Stators of Axial Compressors

Abstract: The paper describes an advanced three-dimensional blading concept for highly loaded transonic compressor stators. The concept takes advantage of the aerodynamic effects of sweep and dihedral. To the knowledge of the authors this is the first approach reported in the open literature that combines those two basic types of lean in an engine-worthy aerofoil design. The paper makes a contribution to the understanding of the endwall effect of both features with special emphasis put on sweep. The advanced three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…As the core component in gas turbines, multi-stage compressors are continuously developed to achieve higher stage loading, making it critical to capture the aerodynamic performances during the design and optimization processes. 20,21 However, there seems to be very little discussion in the literature about the detailed aerodynamic analysis on highly loaded compressor in semi-closed cycles. In the previous studies, the investigations are mainly on the overall characteristic of the components, and few data are available regarding the particular aerodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As the core component in gas turbines, multi-stage compressors are continuously developed to achieve higher stage loading, making it critical to capture the aerodynamic performances during the design and optimization processes. 20,21 However, there seems to be very little discussion in the literature about the detailed aerodynamic analysis on highly loaded compressor in semi-closed cycles. In the previous studies, the investigations are mainly on the overall characteristic of the components, and few data are available regarding the particular aerodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of blade sweep include the influence of secondary flow and radial redistribution despite shockwave control. Gu¨mmer et al 11 investigated the sweep and dihedral effects in stators of axial compressors both numerically and experimentally and demonstrated that positive sweep and positive dihedral could reduce endwall losses and increase operating ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Tubbs H et al [8] demonstrated a 1 percent rise of efficiency and 6 percent rise of surge margin for the high pressure compressor of IAE V2500 engine by adopting end-bent CDA blades. V. Gümmer et al [9] applied an advanced 3-D blading concept to an engine section stator of the BR710 engine, finding that positive sweep and positive dihedral could reduce endwall losses and largely alleviate the hub corner stall.…”
Section: Introductionmentioning
confidence: 98%